2012
DOI: 10.1371/journal.pone.0040443
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-411 Is a Vascular Ligand for MCAM and Facilitates TH17 Cell Entry into the CNS

Abstract: TH17 cells enter tissues to facilitate pathogenic autoimmune responses, including multiple sclerosis (MS). However, the adhesion molecules involved in the unique migratory capacity of TH17 cells, into both inflamed and uninflamed tissues remain unclear. Herein, we characterize MCAM (CD146) as an adhesion molecule that defines human TH17 cells in the circulation; following in vitro restimulation of human memory T cells, nearly all of the capacity to secrete IL-17 is contained within the population of cells expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 51 publications
8
114
3
1
Order By: Relevance
“…Although it has been reported that CD146 acts as a homophilic adhesion molecule, we (4) and others (25) have not been able to show a direct interaction between sCD146 and membrane CD146 or between membrane CD146 and itself. Along this line, two different heterophilic ligands of membrane CD146 have been recently described.…”
Section: Discussioncontrasting
confidence: 91%
“…Although it has been reported that CD146 acts as a homophilic adhesion molecule, we (4) and others (25) have not been able to show a direct interaction between sCD146 and membrane CD146 or between membrane CD146 and itself. Along this line, two different heterophilic ligands of membrane CD146 have been recently described.…”
Section: Discussioncontrasting
confidence: 91%
“…It is clear that T H 17 cells have additional adhesive mechanisms that permit CNS entry even in the presence of natalizumab. LFA-1 is likely to play an important role, consistent with the findings of Rothhammer et al (Rothhammer et al, 2011) in EAE using conditional 4 integrin knockout mice and potentially also MCAM/laminin, which is consistent with the results from Flanagan et al (2012) and . We hypothesize that the cells that are still able to enter the CSF in natalizumab-treated patients are most likely to be T H 17 cells, suggesting a role for this population not only in FCS and Hepes).…”
Section: Methodssupporting
confidence: 89%
“…Our study supports the relevance of these findings in the human system as MCAM + memory cells (T H 17 cells; Flanagan et al, 2012;Larochelle et al, 2012) could still adhere to endothelium under CD49d-blocking conditions. An additional blockade of LFA-1 could abrogate this adhesion, in accordance with previously published data, suggesting that LFA-1 is important for the CNS infiltration of all T cells (Rothhammer et al, 2011).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Although the roles of ICAM-1 and VCAM-1 during leukocyte transmigration in most vascular beds have been extensively studied (8)(9)(10), additional adhesion molecules have also been shown to partake in the transmigration process of encephalitogenic immune cells, including activated leukocyte cell adhesion molecule (ALCAM/CD166) (11,12), melanoma cell adhesion molecule (MCAM) (13)(14)(15), mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) (16,17), vascular adhesion protein (VAP-1) (18,19), Ninjurin-1 (20), and JAM-L (21). We have previously demonstrated that ALCAM is part of a group of adhesion molecules, found on BBB endothelial cells (BBB-ECs), that are involved in immune cell diapedesis (11,12).…”
mentioning
confidence: 99%